Emergent Institutional Issues from New Tenure Reforms and Social-Forestry Initiatives in Indonesia: Notes from The Field - Kusuma, Aprisep Ferdhana; Sahide, Muhammad Alif K.; Purwanto, Ris Hadi; Ismariana, Ema; Santoso, Widodo Budi; Wulandari , Eka; Maryudi, Ahmad (Forest and Society, 2023)
In Indonesia, land tenure reform has been approached as a policy priority by the government to address rural poverty and achieve distributive economic equity. It is instituted around allocation and consolidation of land ownership and access. Tenure reform policy promises over 21.7 million hectares (including 16.8 million hectares of forestland) to be distributed through two modes, i.e., land subject to agrarian reform and social forestry. Specifically for Java, the country’s most populated island, the government has recently allocated 1.1 million hectares of state forests to be entrusted to local communities in a scheme called Kawasan Hutan Dengan Pengelolaan Khusus/KHDPK (Forest Zones for Special Management Purposes). Approximately three-quarters of the KHDPK-reserved forestland is pledged for SF licensing/permits to be completed by 2024. Currently, there is heightened activity to hand over social forestry permits. However, the KHDPK-designated forest is not an unoccupied resource that can simply be transferred/granted to local communities. From only four sites, we discovered that the forests have been guided by contrasting (often conflicting) principles, norms, and values that have shaped the existing tenure arrangements, how it is used and managed, and by whom. Such issues must be navigated prior to introducing the new policy and implementation regime. We conclude that while the policy rationales look perfect as a framework, KHDPK implementation exhibits impediments and potential failures. There is risk of altering it into a mere industry of policy rhetoric, sustaining major flaws from design to execution.